Damage propagation analysis of composite laminates with double-spiral-damage subjected to compressive load - Makoto ICHIKI; Hiroshi SUEMASU (Nihon Kikai Gakkai ronbunshu, 2015)
Failure mechanism of composite laminates with impact damage subjected to compression was studied using finite element analysis. The impact damage was modeled as a double-spiral-damage which consisted of fan-shaped delaminations and matrix cracks. Cohesive element was used to simulate the damage growth. First, the damage growth before the unstable propagation of the damage was discussed from the results of static implicit analysis. Next, the failure process of laminate was analyzed by a dynamic explicit analysis. The damage grew in the transverse direction to the compressive load due to the through-thickness local buckling of the damaged area. Unstable propagation of the damage accompanying large load drop occurred suddenly after the small stable growth of the damage. The transverse damage sizes of all delaminations tended to become in equal size.